Caudal vena cava measurements and fluid responsiveness in hospitalized cats with compromised hemodynamics and tissue hypoperfusion. Issue 1 (20th December 2022) - Donati, Pablo A.; Tunesi, Marcela; Araos, Joaquin
Abstract: Objective: To evaluate the use of the caudal vena cava collapsibility index (CVCCI) and the inspiratory/minimum and expiratory/maximum diameters of the vena cava to predict fluid responsiveness in hospitalized, critically ill cats with hemodynamic and tissue perfusion abnormalities. Design: Diagnostic test study in a prospective cohort of hospitalized cats. Setting: Private practice referral hospital. Animals: Twenty‐four hospitalized cats with spontaneous breathing and compromised hemodynamics and tissue hypoperfusion. Interventions: Ultrasonographic examination before and after fluid expansion with 10 ml/kg of lactated Ringer's solution. Measurements and Main Results: Fluid responsiveness was evaluated using the velocity–time integral (VTI) of the subaortic blood flow, by measuring it before and after a fluid load of 10 ml/kg of lactated Ringer's solution. The CVCCI was calculated using the following formula: (maximum diameter – minimum diameter / maximum diameter) × 100. Ten cats were fluid responders (42 %) and 14 were nonresponders (58 %). The area under the receiver operating characteristic curve (AUROC) with their 95% confidence interval for the predictors and the best cutoff values were as follows: CVCCI, AUROC = 0.83 (0.66–1.00) and cutoff = 31%; inspiratory/minimum diameter, AUROC = 0.86 (0.70–1.00) and cutoff = 0.24 cm; expiratory/maximum diameter, AUROC = 0.88 (0.74–1.00) and cutoff = 0.22 cm. A significant lineal correlation was observed between the percentage of increase in VTI after expansion and CVCCI ( r s = 0.68, P < 0.001), expiratory/maximum diameter ( r s = –0.72, P < 0.001), and inspiratory/minimum diameter ( r s = –0.71, P < 0.001). The intraobserver and interobserver variability was low for VTI, and the expiratory/maximum diameter and inspiratory/minimum diameter were high for CVCCI. Conclusions: Caudal vena cava measurements could be useful to predict the response to fluids in hospitalized cats with hemodynamic and tissue perfusion alterations. Additional studies are required to draw definitive conclusions about the role of these variables to guide fluid administration in cats.